Roles of tumor-associated neutrophils in tumor metastasis and its clinical applications - Yan, Man; Zheng, Minying; Niu, Rui; Yang, Xiaohui; Tian, Shifeng; Fan, Linlin; Li, Yuwei; Zhang, Shiwu (Frontiers in Cell and Developmental Biology, 2022)
Metastasis, a primary cause of death in patients with malignancies, is promoted by intrinsic changes in both tumor and non-malignant cells in the tumor microenvironment (TME). As major components of the TME, tumor-associated neutrophils (TANs) promote tumor progression and metastasis through communication with multiple growth factors, chemokines, inflammatory factors, and other immune cells, which together establish an immunosuppressive TME. In this review, we describe the potential mechanisms by which TANs participate in tumor metastasis based on recent experimental evidence. We have focused on drugs in chemotherapeutic regimens that target TANs, thereby providing a promising future for cancer immunotherapy.